Plated steel sheet
By adjusting the chemical composition and manufacturing conditions of the plating layer, a coated steel plate with high plane corrosion resistance and coating adhesion is formed, which solves the problem of poor plating performance in the prior art, and realizes a high-performance plating for building materials. .
Patent Information
- Application Number
- CN202380047404.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-22
- Filing Date
- 2023-06-19
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to achieve high plane corrosion resistance and coating adhesion of coatings in the use of roofs, wall materials and other building materials, especially the technology that takes into account both properties has not been fully studied.
By adjusting the chemical composition and manufacturing conditions of the plating layer, ensure that the content of Al, Mg, Ca and Zn in the plating layer is within a specific range, and a large number of Al-Si-Zn-Ca phases are formed on the surface of the plating layer to reduce the Ca-Zn phase. Crystallization, thereby improving planar corrosion resistance and coating adhesion.
It has achieved significant improvements in flat corrosion resistance and coating adhesion of plated steel plates, meeting the high requirements for plating performance of building materials.
Smart Images

Figure BDA0005189865020000211 
Figure BDA0005189865020000221 
Figure BDA0005189865020000231
Abstract
Description
Technical Field
[0001] The present invention relates to a plated steel sheet.
[0002] This application claims priority based on Japanese Patent Application No. 2022-100352 filed in Japan on June 22, 2022, and the contents are incorporated herein by reference. Background Art
[0003] Zn-Al-Mg hot-dip plated steel sheets having a hot-dip Zn plating layer containing Al and Mg have excellent corrosion resistance and are therefore widely used as materials for structural members requiring corrosion resistance, such as building materials.
[0004] For example, Patent Document 1 describes a plated steel material comprising a steel material and a plating layer comprising a Zn-Al-Mg alloy layer disposed on the surface of the steel material, wherein the Zn-Al-Mg alloy layer has a Zn phase and contains a Mg-Sn intermetallic compound phase in the Zn phase, and the plating layer has the following chemical composition: in terms of mass %, it contains Zn: more than 65.0%, Al: more than 5.0% and less than 25.0%, Mg: more than 3.0% and less than 12.5%, Sn: 0.1% to 20.0%, and impurities, and satisfies the following Formulas 1 to 5.
[0005] Formula 1: Bi+In <Sn
[0006] Formula 2: Y+La+Ce≤Ca
[0007] Formula 3: Si <Sn
[0008] Formula 4: O≤Cr+Ti+Ni+Co+V+Nb+Cu+Mn<0.25
[0009] Formula 5: O≤Sr+Sb+Pb+B<0.5
[0010] Patent document 2 describes a plated steel material, which comprises a steel material and a plating layer arranged on the surface of the steel material and comprising a Zn-Al-Mg alloy layer, wherein in a cross section of the Zn-Al-Mg alloy layer, the area fraction of the MgZn2 phase is 45 to 75%, the combined area fraction of the MgZn2 phase and the Al phase is 70% or more, and the area fraction of the Zn-Al-MgZn2 ternary eutectic structure is 0 to 5%, and the plating layer has the following chemical composition: in terms of mass %, it comprises Zn: more than 44.90% and less than 79.90%, Al: more than 15% and less than 35%, Mg: more than 5% and less than 20%, Ca: more than 0.1% and less than 3.0%, and impurities When element group A is set to Y, La and Ce, element group B is set to Cr, Ti, Ni, Co, V, Nb, Cu and Mn, element group C is set to Sr, Sb and Pb, and element group D is set to Sn, Bi and In, the total content of elements selected from element group A is 0% to 0.5%, the total content of Ca and elements selected from the above element group A is 0.1% or more and less than 3.0%, the total content of elements selected from element group B is 0% to 0.25%, the total content of elements selected from element group C is 0% to 0.5%, and the total content of elements selected from element group D is 0% to 20.00%.
[0011] In recent years, hot-dip galvanized steel materials for building materials used in roofs, wall materials, etc. require both the corrosion resistance of the coating itself, i.e., the flat corrosion resistance, and the adhesion of the coating film when applied to the surface of the coating (coating adhesion). On the other hand, a technology that takes both flat corrosion resistance and coating adhesion into consideration at a high level has not been studied.
[0012] Prior art literature
[0013] Patent Literature
[0014] Patent Document 1: International Publication No. 2018 / 139619
[0015] Patent Document 2: International Publication No. 2018 / 139620 Summary of the invention
[0016] Problems to be solved by the invention
[0017] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a plated steel sheet having both excellent flat corrosion resistance and coating adhesion.
[0018] Means for solving problems
[0019] In order to solve the above-mentioned problems, the present invention adopts the following configuration.
[0020] [1] A plated steel sheet comprising a steel sheet and a plating layer disposed on a surface of the steel sheet,
[0021] The chemical composition of the above-mentioned coating contains, by mass%, the following:
[0022] Al: 10.0-30.0%,
[0023] Mg: 3.0-15.0%,
[0024] Fe: 0.01-2.0%,
[0025] Si: more than 0% and 2.0% or less,
[0026] Ca: 0.05-2.0%,
[0027] further comprising one or two selected from the following Group A and Group B,
[0028] The remainder contains Zn and impurities.
[0029] The number density of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more exposed on the surface of the above-mentioned coating layer is 2 The area is 0 to 10.
[0030] The number density of the Al-Si-Zn-Ca phase with an equivalent circle diameter of 1 μm or more exposed on the surface of the plating layer is 2 The area is 1 to 50.
[0031] [Group A] Ni: 0 to 1.0%
[0032] [Group B] One or more of Sb: 0-0.5%, Pb: 0-0.5%, Cu: 0-1.0%, Sn: 0-2.0%, Ti: 0-1.0%, Cr: 0-1.0%, Nb: 0-1.0%, Zr: 0-1.0%, Mn: 0-1.0%, Mo: 0-1.0%, Ag: 0-1.0%, Li: 0-1.0%, La: 0-0.5%, Ce: 0-0.5%, B: 0-0.5%, Y: 0-0.5%, P: 0-0.5%, Sr: 0-0.5%, Co: 0-0.5%, Bi: 0-0.5%, In: 0-0.5%, V: 0-0.5%, W: 0-0.5%: 0-5% in total
[0033] [2] The plated steel sheet according to [1], wherein the chemical composition of Mg and Si in the plating layer is Mg: 4.5 to 8 mass %, Si: 0.1 to 2 mass %,
[0034] The number density of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more exposed on the surface of the above-mentioned coating layer is 2 The area is 0 to 3.
[0035] [3] The plated steel sheet according to [1], wherein the chemical composition of Al, Mg and Si in the plating layer is Al: 15-25 mass %, Mg: 4.5-8 mass %, Si: 0.1-2 mass %,
[0036] The number density of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more exposed on the surface of the above-mentioned coating layer is 2 The area is 0.
[0037] [4] The plated steel sheet according to any one of [1] to [3], wherein the chemical composition of the coating layer is Al: 15-25 mass %, Mg: 4.5-8 mass %, Si: 0.1-2 mass %,
[0038] The number density of the Mg-Si-Zn-Al phase with a major diameter of 2 μm or more exposed on the surface of the plating layer is 2 The area is 5 to 150.
[0039] [5] The plated steel sheet according to any one of [1] to [3], wherein the chemical composition of the plating layer is Sn: 0.05 to 0.5 mass %,
[0040] In the X-ray diffraction measurement of the above-mentioned coating layer, a Mg2Sn phase was detected in the coating layer.
[0041] [6] The plated steel sheet according to [4], wherein the chemical composition of the plating layer is Sn: 0.05 to 0.5 mass %,
[0042] In the X-ray diffraction measurement of the above-mentioned coating layer, a Mg2Sn phase was detected in the coating layer.
[0043] [7] The plated steel sheet according to [1], wherein the plating layer has a chemical composition containing the group A in terms of mass %.
[0044] [8] The plated steel sheet according to [1], wherein the plating layer has a chemical composition containing the group B in mass %.
[0045] [9] The plated steel sheet according to [1], wherein the number density of the Ca-Zn phase with an equivalent circle diameter of less than 1 μm exposed on the surface of the plated layer is 2 The area is more than 1.
[0046] Effects of the Invention
[0047] According to the above-described aspects of the present invention, it is possible to provide a plated steel sheet having both excellent flat corrosion resistance and excellent coating adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is a schematic cross-sectional view of a plated steel sheet as an embodiment of the present invention. DETAILED DESCRIPTION
[0049] If a Ca-Zn phase is crystallized in the coating and exposed on the surface of the coating, it is possible to promote the corrosion of the tissue or phase around the Ca-Zn phase (especially the Ca-Zn phase with an equivalent circle diameter of 1 μm or more). Therefore, if a coating is formed on the coating where the Ca-Zn phase is exposed, the coating adhesion may be reduced due to the influence of the corrosion products generated around the Ca-Zn phase. The inventors of the present invention have found that in order to improve the coating adhesion, it is necessary to prevent the crystallization of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more, which promotes the corrosion of the surrounding metal tissue or phase, as much as possible on the surface of the coating.
[0050] In order to prevent the crystallization of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more, it is sufficient to reduce the Ca content of the coating, but on the other hand, if Ca is contained in the coating, it is expected that the flat corrosion resistance will be improved. Therefore, if Ca is contained and the crystallization of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more can be suppressed on the surface of the coating, it is expected that both the flat corrosion resistance and the coating adhesion can be improved.
[0051] Therefore, the inventors of the present invention conducted intensive research to improve both the flat corrosion resistance and coating adhesion of the coating containing Al, Mg, Ca and Zn, and found that it is effective to form a large amount of Ai-Si-Zn-Ca phase in order to suppress the crystallization of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more. It is speculated that if a large amount of Ai-Si-Zn-Ca phase is formed, the Ca contained in the coating is consumed during the formation of the phase, and the crystallization of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more decreases.
[0052] The inventors of the present invention have conducted research and have found that by adjusting the manufacturing conditions of the coating, a large amount of Ai-Si-Zn-Ca phases are successfully crystallized on the surface of the coating, reducing the Ca-Zn phase with an equivalent circle diameter of 1 μm or more. The coating adhesion is improved by reducing the number density of the Ca-Zn phase at the surface of the coating, and the inclusion of Ca can also improve the flat corrosion resistance.
[0053] Hereinafter, a plated steel sheet as an embodiment of the present invention will be described.
[0054] The plated steel sheet of the present embodiment comprises a steel sheet and a plating layer disposed on the surface of the steel sheet, wherein the chemical composition of the plating layer comprises, by mass%, Al: 10.0 to 30.0%, Mg: 3.0 to 15.0%, Fe: 0.01 to 2.0%, Si: more than 0% and less than 2.0%, Ca: 0.05 to 2.0%, and further comprises one or two selected from the following Group A and Group B, and the remainder comprises Zn and impurities, and the number density of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more exposed on the surface of the plating layer is 2 The area is 0 to 10, and the number density of the Al-Si-Zn-Ca phase with an equivalent circle diameter of 1 μm or more exposed on the surface of the coating layer is per 10000 μm 2 The area is 1 to 50.
[0055] [Group A] Ni: 0 to 1.0%
[0056] [Group B] Sb: 0-0.5%, Pb: 0-0.5%, Cu: 0-1.0%, Sn: 0-2.0%, Ti: 0-1.0%, Cr: 0-1.0%, Nb: 0-1.0%, Zr: 0-1.0%, Mn: 0-1.0%, Mo: 0-1.0%, Ag: 0-1.0%, Li: 0-1.0%, La: 0-0.5%, Ce: 0-0.5%, B: 0-0.5%, Y: 0-0.5%, P: 0-0.5%, Sr: 0-0.5%, Co: 0-0.5%, Bi: 0-0.5%, In: 0-0.5%, V: 0-0.5%, W: 0-0.5% One or more of the following: 0-5% in total
[0057] In the following description, the "%" expression of the content of each element of the chemical composition means "mass %". The content of the elements of the chemical composition is sometimes recorded as element concentration (for example, Zn concentration, Mg concentration, etc.). "Plane corrosion resistance" means the property that the coating layer (specifically, the Zn-Al-Mg alloy layer) itself is not easy to corrode. "Coating adhesion" means the property that the coating film becomes difficult to peel off when a coating film is formed on the coating layer. "Coating" refers to a plated film manufactured by a so-called hot dip coating process.
[0058] like Figure 1 As shown in , the plated steel sheet 1 of the present embodiment has a steel sheet 11. There is no particular limitation on the shape of the steel sheet 11. In addition, the steel sheet 11 may be a base steel sheet formed into a steel pipe, civil engineering materials (gutters, corrugated pipes, gutter covers, anti-sand plates, bolts, metal meshes, guardrails, waterproof walls, etc.), home appliance components (frames of outdoor units of air conditioners, etc.), automobile parts (travel components, etc.), etc. The forming process may be, for example, various plastic processing methods such as pressing, roll forming, and bending.
[0059] There is no particular restriction on the material of the steel plate 11. The steel plate 11 can be, for example, various steel plates such as general steel, Al-killed steel, ultra-low carbon steel, high carbon steel, various high-tensile steels, and some high-alloy steels (steel containing strengthening elements such as Ni and Cr). The steel plate 11 can also be a hot-rolled steel plate, hot-rolled steel strip, cold-rolled steel plate, and cold-rolled steel strip described in JIS G 3302: 2010. There is no particular restriction on the manufacturing method of the steel plate (hot rolling method, pickling method, cold rolling method, etc.) and its specific manufacturing conditions.
[0060] As described below, a steel sheet 11 with adjusted surface roughness is used for the steel sheet to be plated original sheet. The surface roughness of the steel sheet can be adjusted, for example, by setting the surface of the roller or the roller for skin pass rolling to a predetermined surface roughness, transferring the surface shape of the roller during rolling or skin pass rolling, etc.
[0061] The plated steel sheet 1 of the present embodiment has a coating 12 disposed on the surface of a steel sheet 11. The coating 12 of the plated steel sheet 1 of the present embodiment is mainly composed of a Zn-Al-Mg alloy layer due to the chemical composition described later. In addition, the coating 12 of the plated steel sheet 1 of the present embodiment may also include an interface alloy layer having Fe and Al as main components between the steel sheet 11 and the Zn-Al-Mg alloy layer. That is, the coating 12 may be a single-layer structure of a Zn-Al-Mg alloy layer, or a laminated structure including a Zn-Al-Mg alloy layer and an interface alloy layer.
[0062] The chemical composition of the coating of the present embodiment is composed of Zn and other alloying elements. The chemical composition of the coating is described in detail below. It should be noted that the elements whose lower limit of concentration is described as 0% are optional elements, which are not necessary to solve the problem of the plated steel sheet of the present embodiment, but are allowed to be included in the coating for the purpose of improving the characteristics.
[0063] <Al:10.0~30.0%>
[0064] Al contributes to the improvement of plane corrosion resistance, coating adhesion and processability. Therefore, the Al concentration is set to 10.0% or more. The Al concentration can also be set to 11.0% or more, 12.0% or more, or 15.0% or more. On the other hand, in the case of excessive Al, the Mg concentration and the Zn concentration are relatively reduced, and the coating adhesion is deteriorated. Therefore, the Al concentration is set to 30.0% or less. The Al concentration can also be set to 24.0% or less, 22.0% or less, or 20.0% or less.
[0065] <Mg:3.0~15.0%>
[0066] Mg is an element necessary to ensure planar corrosion resistance and paint adhesion. Therefore, the Mg concentration is set to 3.0% or more. The Mg concentration can also be set to 4.0% or more, 5.0% or more, or 6.0% or more. On the other hand, if the Mg concentration is excessive, workability, especially powdering property, may deteriorate, and then planar corrosion resistance may deteriorate. Thus, the Mg concentration is set to 15.0% or less. The Mg concentration can also be set to 10.0% or less or 8.0% or less.
[0067] <Fe: 0.01% - 2.0%>
[0068] The concentration of Fe can also be 0%, but the coating may contain 0.01% or more of Fe. It has been confirmed that if the Fe concentration is 2.0% or less, there is no adverse effect on the properties of the coating. The Fe concentration can also be set, for example, to 0.05% or more, 0.1% or more, 0.5% or more, or 1.0% or more. The Fe concentration is set to 2.0% or less. The Fe concentration can also be set to 1.8% or less or 1.5% or less. Since Fe may be mixed in from the base steel plate, the Fe concentration can also be 0.05% or more.
[0069] <Si: more than 0% and 2.0% or less>
[0070] Si contributes to the improvement of planar corrosion resistance. In addition, it is necessary to crystallize the Al-Si-Zn-Ca phase. Therefore, the Si concentration can also be set to more than 0%, 0.01% or more, 0.02% or more, or 0.06% or more. On the other hand, if the Si concentration is excessive, planar corrosion resistance and paint adhesion deteriorate. Therefore, the Si concentration is set to 2.0% or less. The Si concentration can also be set to 1.8% or less, 1.6% or less, 1.2% or less, or 1.0% or less.
[0071] <Ca: 0.05% - 2.0%>
[0072] Ca is an element that contributes to the improvement of planar corrosion resistance and is an element that can adjust the optimal Mg dissolution amount for imparting planar corrosion resistance. In addition, Ca is necessary to crystallize the Al-Si-Zn-Ca phase. Therefore, the Ca concentration is set to 0.05% or more. Ca can also be 0.10% or more, and can also be 0.20% or more. When Ca is set to 0.10%, the density of the Ca-Zn phase with an equivalent circle diameter of less than 1 μm is likely to be 1 or more. On the other hand, if the Ca concentration is excessive, paint adhesion deteriorates. Therefore, the Ca concentration is set to 2.0% or less. The Ca concentration can also be set to 1.0% or less.
[0073] Furthermore, the coating of the present embodiment may also contain one or two selected from the following Group A or Group B.
[0074] [Group A] Ni: 0 to 1.0%
[0075] [Group B] One or more of Sb: 0 to 0.5%, Pb: 0 to 0.5%, Cu: 0 to 1.0%, Sn: 0 to 2.0%, Ti: 0 to 1.0%, Cr: 0 to 1.0%, Nb: 0 to 1.0%, Zr: 0 to 1.0%, Mn: 0 to 1.0%, Mo: 0 to 1.0%, Ag: 0 to 1.0%, Li: 0 to 1.0%, La: 0 to 0.5%, Ce: 0 to 0.5%, B: 0 to 0.5%, Y: 0 to 0.5%, P: 0 to 0.5%, Sr: 0 to 0.5%, Co: 0 to 0.5%, Bi: 0 to 0.5%, In: 0 to 0.5%, V: 0 to 0.5%, W: 0 to 0.5%: Total is 0 to 5%
[0076] <Ni: 0 to 1.0%>
[0077] The concentration of Ni in Group A can also be 0%. On the other hand, Ni helps to improve the coating adhesion. Therefore, the Ni concentration can also be set at 0.05% or more, 0.08% or more, or 0.1% or more. On the other hand, if the Ni concentration is excessive, the planar corrosion resistance deteriorates. Therefore, the Ni concentration is set at 1.0% or less. The Ni concentration can also be set at 0.8% or less, 0.6% or less, or 0.5% or less.
[0078] Furthermore, in the coating of this embodiment, as Group B, it can also contain one or more elements of Sb: 0 to 0.5%, Pb: 0 to 0.5%, Cu: 0 to 1.0%, Sn: 0 to 2.0%, Ti: 0 to 1.0%, Cr: 0 to 1.0%, Nb: 0 to 1.0%, Zr: 0 to 1.0%, Mn: 0 to 1.0%, Mo: 0 to 1.0%, Ag: 0 to 1.0%, Li: 0 to 1.0%, La: 0 to 0.5%, Ce: 0 to 0.5%, B: 0 to 0.5%, Y: 0 to 0.5%, P: 0 to 0.5%, Sr: 0 to 0.5%, Co: 0 to 0.5%, Bi: 0 to 0.5%, In: 0 to 0.5%, V: 0 to 0.5%, W: 0 to 0.5%. The total of these elements is set at 0 to 5%. If the total exceeds 5%, the planar corrosion resistance or coating adhesion may decrease.
[0079] <Sb, Pb: 0 to 0.5% respectively>
[0080] The concentrations of Sb and Pb can also be 0%. On the other hand, Sb and Pb contribute to the improvement of coating adhesion. Therefore, the concentrations of Sb and Pb can also be set at 0.05% or more, 0.10% or more, or 0.15% or more, respectively. On the other hand, if the concentrations of Sb and Pb are excessive, the planar corrosion resistance deteriorates. Therefore, the concentrations of Sb and Pb are set at 0.5% or less, respectively. The concentrations of Sb and Pb can also be set at 0.4% or less, 0.3% or less, or 0.25% or less, respectively.
[0081] <Cu, Ti, Cr, Nb, Zr, Mn, Mo, Ag and Li: are 0 to 1.0% respectively>
[0082] The concentrations of Cu, Ti, Cr, Nb, Zr, Mn, Mo, Ag and Li can also be 0% respectively. On the other hand, they contribute to the improvement of coating adhesion. Therefore, the concentrations of Cu, Ti, Cr, Nb, Zr, Mn, Mo, Ag and Li can also be set at 0.05% or more, 0.08% or more, or 0.10% or more, respectively. On the other hand, if the concentrations of Cu, Ti, Cr, Nb, Zr, Mn, Mo, Ag and Li are excessive, the planar corrosion resistance deteriorates. Therefore, the concentrations of Cu, Ti, Cr, Nb, Zr, Mn, Mo, Ag and Li are set at 1.0% or less, respectively. The concentrations of Cu, Ti, Cr, Nb, Zr, Mn, Mo, Ag and Li can also be set at 0.8% or less, 0.7% or less, or 0.6% or less, respectively.
[0083] <Sn: 0 to 2.0%>
[0084] The Sn concentration can also be 0%. On the other hand, Sn is an element that forms an intermetallic compound with Mg and improves the coating adhesion of the coating. Therefore, the Sn concentration can also be set at 0.05% or more, 0.1% or more, or 0.2% or more. However, if the Sn concentration is excessive, the planar corrosion resistance deteriorates. Therefore, the Sn concentration is set at 2.0% or less. The Sn concentration can also be set at 1.0% or less, 0.8% or less, or 0.5% or less.
[0085] <La, Ce, B, Y, P and Sr: are 0 to 0.5% respectively>
[0086] The concentration of each of La, Ce, B, Y, P, and Sr may also be 0%. On the other hand, La, Ce, B, Y, P, and Sr contribute to the improvement of coating adhesion. Therefore, the concentration of each of La, Ce, B, Y, P, and Sr may also be set to 0.10% or more, 0.15% or more, or 0.20% or more. On the other hand, if the concentration of La, Ce, B, Y, P, and Sr is excessive, the planar corrosion resistance deteriorates. Therefore, the concentration of each of La, Ce, B, Y, P, and Sr is set to 0.5% or less. The concentration of each of La, Ce, B, Y, P, and Sr may also be set to 0.4% or less, 0.3% or less.
[0087] <Co, Bi, In, V, W: 0 to 0.5% respectively>
[0088] The concentration of each of Co, Bi, In, V, and W may also be 0%. On the other hand, Co, Bi, In, V, and W contribute to the improvement of coating adhesion. Therefore, the concentration of each of Co, Bi, In, V, and W may also be set to 0.10% or more, 0.15% or more, or 0.20% or more. On the other hand, if the concentration of Co, Bi, In, V, and W is excessive, the planar corrosion resistance deteriorates. Therefore, the concentration of each of Co, Bi, In, V, and W is set to 0.5% or less. The concentration of each of Co, Bi, In, V, and W may also be set to 0.4% or less, 0.3% or less.
[0089] <The balance: Zn and impurities>
[0090] The balance of the components of the coating layer of the present embodiment is Zn and impurities. Zn is an element that imparts planar corrosion resistance and coating adhesion to the coating layer. Impurities refer to components contained in the raw materials, or components mixed in during the manufacturing process, and are components that are not intentionally contained. For example, in the coating layer, it is possible that components other than Fe are also slightly mixed as impurities through the mutual atomic diffusion between the base steel plate and the plating bath.
[0091] The chemical composition of the coating layer is measured by the following method. First, the coating layer is stripped and dissolved using an acid containing an inhibitor that suppresses the corrosion of the steel plate to obtain an acid solution. Next, the obtained acid solution is subjected to inductively coupled plasma (ICP) optical emission spectrometry. Thereby, the chemical composition of the coating layer can be obtained. The type of acid is not particularly limited as long as it can dissolve the coating layer. It should be noted that the chemical composition measured by the above means is the average chemical composition of the entire coating layer.
[0092] Next, the metal structure of the coating layer will be described.
[0093] On the surface of the coating of this embodiment, the Ca-Zn phase with an equivalent circle diameter of 1 μm or more should not be allowed to crystallize as much as possible. The number density of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more on the surface is per 10000 μm. 2 0 to 10. If the Ca-Zn phase with an equivalent circle diameter of 1 μm or more is exposed on the surface of the coating, corrosion products are formed around the Ca-Zn phase with an equivalent circle diameter of 1 μm or more at the initial stage of corrosion of the coating, and the coating adhesion is reduced due to the corrosion products. Therefore, the number density of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more is preferably low, and the most preferred number density is 0 (pieces / 10000 μm 2 ). If the number density is per 10000μm 2 If the number exceeds 10, the coating adhesion will decrease, which is not preferred. 2 ), the number density of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more may be 5 or less, or 3 or less.
[0094] Electron beam microanalyzer (EPMA) is used to determine the Ca-Zn phase on the surface of the coating. The surface of the coating is observed using a scanning electron microscope attached to the EPMA to determine the intermetallic compound of the analysis object. Then, elemental analysis is performed on the determined intermetallic compound to determine whether the intermetallic compound is a Ca-Zn phase. Regarding the determination of the Ca-Zn phase, an intermetallic compound containing 35 to 65 atomic % of Ca and more than 35 atomic % of Zn is considered a Ca-Zn phase. In the Ca-Zn phase, Mg, Al, Si, and Fe may also be contained in the range of less than 10 atomic %, respectively.
[0095] Since the Ca-Zn phase with an equivalent circle diameter of 1 μm or more has an adverse effect on the coating adhesion, the crystallization of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more is limited. On the other hand, since the Ca-Zn phase with an equivalent circle diameter of less than 1 μm has basically no effect on the coating adhesion, there is no problem in the present embodiment. The Ca-Zn phase with an equivalent circle diameter of less than 1 μm is not easy to cause corrosion of the surrounding metal structure and phase. Therefore, it is preferred that a Ca-Zn phase with an equivalent circle diameter of less than 1 μm is formed on the surface of the coating. Therefore, on the surface of the coating of the present embodiment, the number density of the Ca-Zn phase with an equivalent circle diameter of less than 1 μm is preferably 1 μm per 10,000 μm. 2 When the unit is set to (pieces / 10000μm 2 ), the number density of the Ca-Zn phase with an equivalent circle diameter of less than 1 μm may be 100 or less, or 50 or less. A more preferred number density of the Ca-Zn phase with an equivalent circle diameter of less than 1 μm is 10 / 10000 μm.2 the following.
[0096] The equivalent circle diameter of the Ca—Zn phase was determined by observing the Ca—Zn phase with a scanning electron microscope and the diameter of a circle having the area was taken as the equivalent circle diameter of the Ca—Zn phase.
[0097] The number density of the Ca-Zn phase on the surface of the coating may be affected by the average chemical composition of the coating. When the chemical composition of the coating is Mg: 4.5-8 mass % and Si: 0.1-2 mass %, the number density of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more exposed on the surface of the coating may be 10000 μm. 2 The area becomes 0 to 3.
[0098] In addition, when the chemical composition of Al, Mg and Si in the plating layer is Al: 15-25 mass%, Mg: 4.5-8 mass%, Si: 0.1-2 mass%, the number density of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more exposed on the surface of the plating layer may be 10000 μm 2 The area becomes 0.
[0099] Next, on the surface of the plating layer of this embodiment, an Al-Si-Zn-Ca phase with an equivalent circle diameter of 1 μm or more is exposed. The number density of the Al-Si-Zn-Ca phase on the surface is 10000 μm 2 1 to 50. The Al-Si-Zn-Ca phase is exposed on the surface of the coating, so that the Ca contained in the coating is consumed for the formation of the phase, and the crystallization of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more can be suppressed. As a result, the coating adhesion is improved. By operating like this, the flat corrosion resistance and coating adhesion of the coating can be improved.
[0100] For the determination of the Al-Si-Zn-Ca phase in the coating, an electron beam microanalyzer (EPMA) is used. The surface of the coating is observed using a scanning electron microscope attached to the EPMA to determine the intermetallic compound of the analysis object. Then, by performing elemental analysis on the determined intermetallic compound, it is determined whether the intermetallic compound is an Al-Si-Zn-Ca phase. Regarding the determination of the Al-Si-Zn-Ca phase, an intermetallic compound containing 20 to 80 atomic % of Zn, 1 to 10 atomic % of Si, 5 to 25 atomic % of Ca, and the remainder being Al (Al: 10 atomic % or more) and 0 to 5 atomic % of other elements is considered an Al-Si-Zn-Ca phase. As other elements other than Al, Si, Zn and Ca, any element contained in the coating can be used.
[0101] If the size of the Al-Si-Zn-Ca phase is small, the crystallization of the Ca-Zn phase cannot be effectively suppressed. Therefore, the size of the Al-Si-Zn-Ca phase with a limited number density needs to be 1 μm or more in terms of equivalent circle diameter. The Al-Si-Zn-Ca phase with an equivalent circle diameter of 1 μm has a number density of 1 (pieces / 10000 μm 2 ) or more, thereby being able to fully suppress the crystallization of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more. Regarding the equivalent circle diameter of the Al-Si-Zn-Ca phase, the area of each Al-Si-Zn-Ca phase is obtained when the Al-Si-Zn-Ca phase is observed with a scanning electron microscope, and the diameter of the circle having the area is taken as the equivalent circle diameter of the Al-Si-Zn-Ca phase.
[0102] The number density of the Al-Si-Zn-Ca phase at the surface of the coating is set to 10000 μm 2 1 to 50. Number density is less than 1 (piece / 10000μm 2 ), the crystallization of the Ca-Zn phase cannot be suppressed, and the coating adhesion becomes insufficient. On the other hand, even if the number density of the Al-Si-Zn-Ca phase exceeds 50 (pieces / 10000 μm 2 ), the effect of improving the coating adhesion is also saturated, so 50 (pieces / 10000μm 2 ) is set as the upper limit. When the unit is set to (pieces / 10000μm 2 ), the number density of the Al-Si-Zn-Ca phase may be greater than 3, or greater than 5. In addition, the number density of the Al-Si-Zn-Ca phase may be less than 40, less than 30, or less than 20.
[0103] Next, on the surface of the plating layer of this embodiment, a Mg-Si-Zn-Al phase with a major diameter of 2 μm or more may be exposed. The number density of the Mg-Si-Zn-Al phase on the surface is 10000 μm 2 5 to 150. If the Mg-Si-Zn-Al phase is exposed on the surface of the plating layer, the Mg-Si-Zn-Al phase is corroded at the initial stage of corrosion of the plating layer, thereby forming a dense corrosion product from Mg, Si, Zn, and Al. By forming this corrosion product, the flat corrosion resistance of the plating layer is further improved.
[0104] An electron beam microanalyzer (EPMA) is used to determine the Mg-Si-Zn-Al phase of the coating. The surface of the coating is observed using a scanning electron microscope attached to the EPMA to determine the intermetallic compound to be analyzed. Then, elemental analysis is performed on the determined intermetallic compound to determine whether the intermetallic compound is a Mg-Si-Zn-Al phase. Regarding the determination of the Mg-Si-Zn-Al phase, an intermetallic compound containing Mg: 20 to 45 atomic %, Si: 15 to 40 atomic %, Zn: 15 to 40 atomic %, and Al: 5 to 20 atomic % is defined as a Mg-Si-Zn-Al phase.
[0105] The number density of the Mg-Si-Zn-Al phase at the surface of the coating is affected by the average chemical composition of the coating. 2 The number of Al, Mg and Si in the chemical composition of the plating layer is preferably 5 to 150, and Al: 15 to 25 mass %, Mg: 4.5 to 8 mass %, and Si: 0.1 to 2 %.
[0106] The shape of the Mg-Si-Zn-Al phase preferably has a long diameter of 2 μm or more, and more preferably a needle shape with a long diameter of 2 μm or more. Furthermore, the aspect ratio is preferably greater than 2. By setting the shape of the Mg-Si-Zn-Al phase to a shape with a long diameter of 2 μm or more, the Mg-Si-Zn-Al phase becomes easily dissolved in the early stage of corrosion, and more dense corrosion products can be formed, which can improve the flat corrosion resistance.
[0107] The major axis of the Mg-Si-Zn-Al phase is set to the maximum length of the Mg-Si-Zn-Al phase when the Mg-Si-Zn-Al phase is observed with an electron microscope. The aspect ratio is the ratio of the major axis to the minor axis (major axis / minor axis). The minor axis is the length in the direction orthogonal to the direction of the major axis, and more specifically, is set to the maximum length within the range of ±5° relative to the orthogonal direction of the major axis.
[0108] The number density of the Mg-Si-Zn-Al phase at the surface of the plating layer is preferably 2 The number density is set to 5 (pieces / 10000 μm 2 ) or more, the flat corrosion resistance can be further improved. On the other hand, even if the number density of the Mg-Si-Zn-Al phase exceeds 150 ( / 10000 μm 2 ), the effect of improving the flat corrosion resistance is also saturated, so 150 (pieces / 10000μm 2 ) is set as the upper limit. When the unit is set to (pieces / 10000μm 2), the number density of the Mg-Si-Zn-Al phase may be greater than 10, or greater than 15. In addition, the number density of the Mg-Si-Zn-Al phase may be less than 120, less than 100, less than 80, less than 70, less than 50, or less than 30.
[0109] It should be noted that the Mg-Si-Zn-Al phase can also be 2 An area greater than 0 and a number density less than 5 exist on the surface of the coating.
[0110] The method for measuring the number density of Ca-Zn phase, Al-Si-Zn-Ca phase and Mg-Si-Zn-Al phase is described. A 50μm square measurement area is set on the surface of the coating. The measurement area is set to 8 locations, and 8 measurement areas are randomly configured on the surface of the coating. The measurement areas are separated in a non-overlapping manner. The intermetallic compound is confirmed by observing the set measurement area with a scanning electron microscope. Then, the composition of the intermetallic compound is analyzed by EPMA to distinguish the Ca-Zn phase, Al-Si-Zn-Ca phase and Mg-Si-Zn-Al phase. Furthermore, the number of Ca-Zn phases with an equivalent circle diameter of more than 1μm, Al-Si-Zn-Ca phases with an equivalent circle diameter of more than 1μm, and Mg-Si-Zn-Al phases with a long diameter of more than 2μm in each measurement area is measured. The measurement conditions of EPMA are set, for example, as follows: the acceleration voltage is 15kV, the current is 0.05μA, and the irradiation time is 50ms. As EPMA, for example, JXA-8230 manufactured by JEOL Ltd. is used.
[0111] It is possible that part of the Ca-Zn phase, Al-Si-Zn-Ca phase and Mg-Si-Zn-Al phase is within the measurement area and the rest of the phase is outside the measurement area, but such phases are also included in the number of measurement objects.
[0112] In addition, when the Mg-Si-Zn-Al phase is needle-shaped, multiple Mg-Si-Zn-Al phases may overlap each other. In such a case, when the major axis directions of the phases overlap in different directions, the overlapping phases are measured as the number of phases. For example, when two Mg-Si-Zn-Al phases overlap each other and their major axis directions are in different directions, the number is counted as 2.
[0113] Then, based on the number of Ca-Zn phases with an equivalent circle diameter of 1 μm or more, Al-Si-Zn-Ca phases with an equivalent circle diameter of 1 μm or more, and Mg-Si-Zn-Al phases with a major diameter of 2 μm or more measured in the eight measurement areas and the total area of the measurement areas, the number of phases per 10,000 μm was calculated. 2 The number of is taken as the number density.
[0114] In addition, when the coating contains 0.05 to 0.5 mass % Sn, it is preferred that the coating contain Mg2Sn phase. Since the Mg2Sn phase is a small amount, its presence is detected and confirmed by X-ray diffraction measurement. By containing the Mg2Sn phase in the coating, the corrosion resistance of the coating is further improved. Whether the coating contains the Mg2Sn phase is determined by whether a diffraction peak unique to Mg2Sn appears. Here, the diffraction peak unique to Mg2Sn refers to, for example, a peak that appears when the diffraction angle 2θ is 23.4 ± 0.3 degrees.
[0115] The coating weight per single side of the plating layer is set to, for example, 20 to 150 g / m 2 By setting the adhesion amount per single side to 20g / m 2 The above can further improve the flat corrosion resistance and coating adhesion of the plated steel sheet. On the other hand, by setting the adhesion amount per single side to 150 g / m 2 Next, the workability of the plated steel sheet can be further improved.
[0116] Next, a method for producing a plated steel sheet according to the present embodiment will be described, but the method for producing a plated steel sheet according to the present embodiment is not particularly limited. For example, the plated steel sheet according to the present embodiment can be obtained according to the production conditions described below.
[0117] The manufacturing method of the plated steel sheet of the present embodiment is to anneal the steel sheet with adjusted surface roughness in a reducing atmosphere, immerse the steel sheet just after annealing in a hot dip coating bath and then pick it up, thereby forming a coating on the surface of the steel sheet. Next, cooling gas is blown during the period from the bath temperature to the coating temperature below 300°C to cool it. Regarding the gas flow when blowing the cooling gas, the gas flow from the bath temperature to the controlled cooling temperature (the gas flow rate in the temperature range above the controlled cooling temperature and below the bath temperature) is set to 100 to 5000 L / min / m 2 The gas flow rate (gas flow rate in the temperature range above the cooling stop temperature and below the controlled cooling temperature) from the controlled cooling temperature to the cooling stop temperature (300°C or less in the present embodiment) is set to 10000 to 80000 L / min / m 2 range.
[0118] The controlled cooling temperature is set to a temperature within a range of -10°C to -80°C with respect to the crystallization temperature of the Al-Si-Zn-Ca phase.
[0119] Regarding the roughness of the surface of the steel sheet to be plated, the length L of the roughness curve per reference length L0 is p The ratio (L p / L0) is set to 1.0 or more, and the arithmetic mean roughness Ra is set to 0.1 μm or more. If it is out of this range, a large amount of Al-Si-Zn-Ca phase may be crystallized near the interface between the coating and the steel sheet, and the number density of the Al-Si-Zn-Ca phase on the surface of the coating is reduced. (L p The upper limit of the arithmetic mean roughness Ra is preferably 3.0 or less, and may be 2.5 or less, or 2.0 or less. The upper limit of the arithmetic mean roughness Ra is preferably 4.0 μm or less, and may be 3.5 μm or less. There is no particular limitation on the adjustment of the roughness of the steel plate surface, but it can be adjusted, for example, by rolling the plated original plate with a roller or a roller for temper rolling whose roller surface is adjusted to the desired roughness to transfer the surface shape of the roller. In addition, it can also be adjusted by pickling.
[0120] (L p / L0) and arithmetic mean roughness are measured, for example, using a shape measurement laser microscope (model: VK-8700) manufactured by KEYENCE Co., Ltd. The measurement conditions are, for example, set to measurement mode: laser confocal, measurement quality: high precision, spacing: 0.75 μm, double scanning: open, optical zoom: 1x, objective lens name: plan achromat (Plan), γ coefficient: 0.45, bias: 0%, and the measurement is performed. It should be noted that (L p The measuring device used in the measurement of (L / L0) and arithmetic mean roughness is not limited to the above example. The roughness curve is obtained by sequentially applying the profile curve filters with cutoff values λc and λs to the cross-sectional curve obtained by measurement in accordance with JIS B 0601:2013. Specifically, the components with wavelength λc of 0.001 mm or less and the components with wavelength λs of 0.2 mm or more are removed from the obtained measurement results to obtain the roughness curve. Based on the obtained roughness curve, (L p / L0) and arithmetic mean roughness.
[0121] Annealing of the steel sheet to be plated is performed in a reducing atmosphere. The reducing atmosphere and annealing conditions are not particularly limited. Through this annealing, oxides present on the surface of the steel sheet are removed as much as possible.
[0122] Next, the steel sheet immediately after annealing is immersed in a hot dip coating bath. The chemical composition of the hot dip coating bath may be appropriately adjusted so as to obtain the chemical composition of the coating layer described above. In addition, the temperature of the hot dip coating bath is not particularly limited, and a temperature at which hot dip coating can be performed may be appropriately selected. For example, the coating bath temperature may be set to a value that is about 20° C. higher than the melting point of the coating bath.
[0123] Next, the steel sheet is scooped out of the hot dip coating bath. By controlling the scooping speed of the steel sheet, the amount of the coating can be controlled. If necessary, the amount of the coating can be controlled by wiping the steel sheet with the coating. The amount of the coating is not particularly limited, and can be set within the above range, for example.
[0124] Next, the coating is cooled. The cooling is performed by blowing cooling gas on the steel sheet just after being taken out of the hot dip coating bath. The cooling by blowing cooling gas is performed continuously during the period when the temperature of the steel sheet increases from the bath temperature to 300°C. The cooling conditions below 300°C are not particularly limited, and cooling by blowing cooling gas or natural cooling may be performed next.
[0125] In the cooling by blowing cooling gas, it is carried out by configuring a cooling belt along the conveying path of the steel plate. In the cooling belt, there are multiple blowing nozzles for cooling gas. The shape of the gas nozzle that sprays the cooling gas is set to a diameter range of 1 to 50 mm, for example. The angle between the front end of the gas nozzle and the steel plate is set to a range of 70 to 110°, more preferably 90° (right angle). The distance between the front end of the gas nozzle and the steel plate is set to a range of 30 to 1000 mm. It should be noted that the shape, angle, and distance of the gas nozzle are simply an example and are not limited to the above range.
[0126] The cooling gas to be blown is not particularly limited, and may be a non-oxidizing gas such as nitrogen, an inert gas such as argon, or air, or a mixed gas thereof.
[0127] In this embodiment, the gas flow when blowing the cooling gas is controlled in two stages. That is, based on the temperature of the steel plate, the gas flow from the coating bath temperature to the controlled cooling temperature (a temperature in the range of -10 to -80°C relative to the crystallization temperature of the Al-Si-Zn-Ca phase) is set to 100 to 5000 L / min / m 2 The range is preferably set to 500 to 5000 L / min / m 2 The gas flow rate from the controlled cooling temperature to below 300°C is set to 10000-80000 L / min / m 2 The controlled cooling temperature is a temperature presumed to be the crystallization start temperature of the Al-Si-Zn-Ca phase.
[0128] When the gas flow is set to 5000L / min / m 2 When the gas flow rate is set to 10000 L / min / m 2 In the case of the above range, it is possible to provide vibration to the steel plate being cooled.
[0129] Furthermore, by setting the gas flow from the coating bath temperature to the controlled cooling temperature to 100 to 5000 L / min / m 2 The range is preferably set to 500 to 5000 L / min / m 2 The range of , thereby promoting the nucleation of Ca-containing phases other than Al-Si-Zn-Ca phases without vibrating the steel plate, so that Ca and Si are concentrated in the unsolidified liquid phase. Next, the gas flow is set to 10000-80000 L / min / m from the controlled cooling temperature to below 300°C. 2 The range of the gas stream is within the above range, so that the surface of the unsolidified liquid phase can be vibrated, and a large amount of Al-Si-Zn-Ca phase can be crystallized on the surface of the coating. If the range of the gas stream deviates from the above range, it becomes difficult to crystallize a large amount of Al-Si-Zn-Ca phase on the surface of the coating.
[0130] The crystallization temperature of the Al-Si-Zn-Ca phase changes according to the chemical composition of the coating, so it is calculated using a calculation state diagram. Specifically, the thermodynamic data of the intermetallic compound phase, the metal phase, etc. that can be contained in the Al-Mg-Zn alloy are concentrated to construct a calculation state diagram database, and the crystallization temperature of the Al-Si-Zn-Ca phase is calculated for each chemical composition of the coating by using the CALPHAD method (phase diagram calculation; CALculation of PHAse Diagram). More specifically, by using the thermodynamic equilibrium calculation software "Thermo-Calc" ((Thermo-Calc is a registered trademark) Thermo-Calc Software Company), the crystallization temperature of the Al-Si-Zn-Ca phase can be estimated. It should be noted that the thermodynamic equilibrium calculation software used in the calculation is not limited to "Thermo-Calc" (registered trademark), and other software can also be used. The temperature in the range of -10 to -80°C relative to the crystallization temperature of the Al-Si-Zn-Ca phase obtained is used as the controlled cooling temperature.
[0131] In the above-mentioned manufacturing method, by pre-adjusting the surface roughness of the steel sheet surface, the nucleation of the Al-Si-Zn-Ca phase can be suppressed, thereby suppressing the crystallization of the Al-Si-Zn-Ca phase inside the coating. By hot-dip coating such a steel sheet and then controlling the cooling conditions after coating as described above, a large amount of Al-Si-Zn-Ca phase is crystallized on the surface of the coating. It is presumed that a large amount of Al-Si-Zn-Ca phase with an equivalent circle diameter of 1 μm or more can be formed on the surface of the coating, and the crystallization of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more can be suppressed.
[0132] It should be noted that as long as the necessary conditions shown in the present invention are met, the method for manufacturing the plated steel sheet is not limited to the above content, and instead of the hot dip method, electroplating, vapor deposition plating, spraying, cold spraying, etc. can also be used.
[0133] Example
[0134] The following is an explanation of the embodiments of the present invention. However, the conditions in the embodiments are only a condition example adopted to confirm the feasibility and effect of the present invention. The present invention is not limited to this condition example. As long as it does not deviate from the main purpose of the present invention and achieves the purpose of the present invention, the present invention can adopt various conditions.
[0135] For the plated original plate, a cold-rolled steel plate (0.05C-0.1Si-0.2Mn) with a plate thickness of 1.2 mm is used. The surface roughness of a portion of the plated original plate is controlled using a skin-pass rolling mill, etc. The steel plate with adjusted surface roughness is annealed. The annealed steel plate is dipped in various hot-dip baths and then scooped up, so that a coating is attached to the surface of the steel plate. Then, various plated steel plates are manufactured by cooling with a cooling gas from the time the steel plate is just scooped up from the plating bath until the coating reaches 300°C.
[0136] The surface roughness of the steel sheet surface to be plated is calculated by calculating the length L of the roughness curve per reference length L0. p The ratio (L p / L0) is set to 1.1 to 2.6, and the arithmetic mean roughness Ra is set to the range of 0.6 to 3.7 μm.
[0137] (L p The measurement of the surface roughness (L / L0) and the arithmetic mean roughness was performed using a shape measurement laser microscope (model: VK-8700) manufactured by KEYENCE Co., Ltd. The measurement conditions were set as follows: measurement mode: laser confocal, measurement quality: high precision, pitch: 0.75 μm, double scanning: open, optical zoom: 1x, objective lens name: plan achromat (Plan), γ coefficient: 0.45, bias: 0%, and the measurement was performed.
[0138] Regarding the annealing conditions when the steel sheet is annealed in a reducing atmosphere, the soaking temperature is set to 600°C and the soaking time is set to 10 seconds. The annealing atmosphere is set to a reducing atmosphere of a mixed gas containing 5% hydrogen and the remainder nitrogen. Then, the annealed steel sheet is air-cooled with nitrogen until the dip plate temperature reaches the bath temperature + 20°C, and then dipped in the hot dip bath and pulled out. The pulling out speed is set to 20 to 200 mm / second.
[0139] The chemical composition of the hot-dip coating is shown in Table 1. The manufacturing conditions were set as shown in Table 2. In addition, the metal structure of the coating was evaluated, and the results are shown in Table 3. Furthermore, the plane corrosion resistance and coating adhesion of the plated steel sheet were evaluated, and the results are shown in Table 3.
[0140] The evaluation of the chemical composition of the coating and the metal structure of the coating is carried out by the above-mentioned means. It should be noted that, with respect to the Ca-Zn phase, the equivalent circle diameter of 1 μm or more and the equivalent circle diameter of less than 1 μm are used as the measurement objects. With respect to the Al-Si-Zn-Ca phase, the equivalent circle diameter of 1 μm or more is used as the measurement object. In addition, with respect to the Mg-Si-Zn-Al phase, the long diameter of 2 μm or more is used as the measurement object. It should be noted that the aspect ratio of the measured Mg-Si-Zn-Al phase is 2 or more.
[0141] The evaluation of plane corrosion resistance is set as follows. The obtained plated steel sheet is cut into 100 mm × 50 mm and provided for the plane corrosion resistance evaluation test. The evaluation of plane corrosion resistance is carried out by the corrosion promotion test specified in JASO-CCT-M609, and is carried out by comparing the corrosion loss after 150 cycles. The evaluation criteria are set as follows, and "AAA", "AA" and "A" are set as qualified.
[0142] AAA: Corrosion loss less than 50g / m 2
[0143] AA: Corrosion loss is 50g / m 2 Above and below 90g / m 2
[0144] A: Corrosion loss is 90g / m 2 Above and below 120g / m 2
[0145] B: Corrosion loss is 120g / m 2 above
[0146] Evaluation of coating adhesion was performed as follows: The obtained plated steel sheet was cut into 100 mm×50 mm and subjected to a coating adhesion test. After forming a coating film layer on the test piece, the end surface and the back surface were sealed with a silicone resin.
[0147] Next, for the front side, a cutter is used to give a cut that reaches the base metal. The cut is given in a grid pattern with an interval of 1 mm. In this way, 100 1 square millimeter areas divided by the cut are formed. Next, it is immersed in a 5% NaCl aqueous solution at 50°C for 500 hours, and after immersion, it is washed with water and dried. Then, for the dried sample, the tape is peeled off after sticking the adhesive tape on the cut part and then tearing it off, and the peeling area rate is measured.
[0148] <Coating layer>
[0149] The coating layer was formed by applying the primer resin and the top coating resin described below on the surface of the plated layer. The thickness of the layer formed by the primer resin was set to 5 μm, and the thickness of the layer formed by the top coating resin was set to 15 μm, and the total thickness was set to 20 μm.
[0150] <Film-forming components of coating layer>
[0151] (1) Primer coating resin for front / back side
[0152] Polyester / melamine + isocyanate combined curing type (FLC687 coating resin manufactured by Japan Fine Coatings Co., Ltd.)
[0153] (2) Front outer coating resin
[0154] Polyester / melamine curing type (FLC7000 coating resin manufactured by Japan Fine Coatings Co., Ltd.)
[0155] (3) Back side outer coating resin
[0156] Polyester / melamine curing type (FLC100HQ coating resin manufactured by Japan Fine Coatings Co., Ltd.)
[0157] The following are the evaluation criteria for coating adhesion. The evaluation was performed using the following scoring system. "AAA", "AA" and "A" were considered acceptable.
[0158] AAA: peeling area rate less than 10%
[0159] AA: The peeling area ratio is 10% or more and less than 20%
[0160] A: The peeling area ratio is 20% or more and less than 30%
[0161] B: The peeling area ratio is 30% or more
[0162] As shown in Tables 1 to 3, Examples 1 to 30 and 39 of the present invention, in which the chemical composition and metal structure of the coating layer are appropriately controlled, have excellent flat corrosion resistance and coating adhesion. It should be noted that the coating weight per single side of the examples is 20 to 150 g / m 2 range.
[0163] In Comparative Example 31, the Al content of the plating layer was insufficient. Therefore, in Comparative Example 31, the crystallization temperature of the Ca-Zn phase increased, and a large amount of Ca-Zn phases with an equivalent circle diameter of 1 μm were crystallized. As a result, the flat corrosion resistance was insufficient.
[0164] In Comparative Example 32, the amount of Al in the plating layer was excessive. Therefore, in Comparative Example 32, a large amount of Ca-Zn phases with an equivalent circle diameter of 1 μm in which Al was solid-dissolved were crystallized. As a result, the coating adhesion was reduced.
[0165] In Comparative Example 33, the Mg content of the plating layer was insufficient. Therefore, in Comparative Example 33, the crystallization temperature of the Ca-Zn phase increased, and a large amount of Ca-Zn phases with an equivalent circle diameter of 1 μm were crystallized. As a result, the flat corrosion resistance and coating adhesion were reduced.
[0166] In Comparative Example 34, the amount of Mg in the plating layer was excessive. Therefore, in Comparative Example 34, the appearance of the plating layer was significantly deteriorated.
[0167] In Comparative Example 35, the Si content of the plating layer was excessive. Therefore, in Comparative Example 35, Si was not crystallized as an Al-Si-Zn-Ca phase but as a Si phase, and thus the crystallization of the Ca-Zn phase with an equivalent circle diameter of 1 μm was not suppressed, and the flat corrosion resistance and coating adhesion were reduced.
[0168] In Comparative Example 36, the amount of Ca in the hot-dip coating was excessive. Therefore, in Comparative Example 36, a Ca-Zn phase with an equivalent circle diameter of 1 μm was excessively crystallized on the surface of the coating, and the flat corrosion resistance and coating adhesion were reduced.
[0169] In Comparative Example 37, the cooling gas flow from the bath temperature to the controlled cooling temperature was excessive. Therefore, in Comparative Example 37, due to the influence of vibration, the nucleation of the Ca-Zn phase with an equivalent circle diameter of 1 μm on the surface of the coating layer progressed, and the flat corrosion resistance and coating adhesion decreased.
[0170] In Comparative Example 38, the cooling gas flow from the cooling temperature to 300° C. was insufficient. Therefore, in Comparative Example 38, sufficient vibration was not given, the formation of the Al-Si-Zn-Ca phase became insufficient, and the Ca-Zn phase with an equivalent circle diameter of 1 μm was crystallized excessively, and the flat corrosion resistance and coating adhesion were reduced.
[0171] [Table 1]
[0172]
[0173] The underlined part indicates that it is outside the scope of the present invention.
[0174] [Table 2]
[0175]
[0176] The underlined portion indicates that the conditions are outside the range of the preferred production conditions.
[0177] [Table 3]
[0178]
[0179] The underlined part indicates that it is outside the scope of the present invention.
[0180] Industrial Applicability
[0181] The plated steel sheet of the present disclosure is excellent in both flat surface corrosion resistance and coating adhesion, and therefore has high industrial applicability.
[0182] Explanation of symbols
[0183] 1 coated steel plate, 11 steel plate, 12 coating.
Claims
1. A plated steel sheet, characterized in that: The invention comprises a steel plate and a plating layer arranged on the surface of the steel plate. The chemical composition of the coating contains, in mass %, Al:10.0~30.0%、 Mg: 3.0-15.0%, Fe: 0.01-2.0%, Si: more than 0% and 2.0% or less, Ca: 0.05-2.0%, further comprising one or two selected from the following Group A and Group B, The remainder contains Zn and impurities. The number density of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more exposed on the surface of the plating layer is 2 The area is 0 to 10. The number density of the Al-Si-Zn-Ca phase with an equivalent circle diameter of 1 μm or more exposed on the surface of the plating layer is 2 The area is 1 to 50. [Group A]Ni: 0~1.0% [Group B] One or more of Sb: 0-0.5%, Pb: 0-0.5%, Cu: 0-1.0%, Sn: 0-2.0%, Ti: 0-1.0%, Cr: 0-1.0%, Nb: 0-1.0%, Zr: 0-1.0%, Mn: 0-1.0%, Mo: 0-1.0%, Ag: 0-1.0%, Li: 0-1.0%, La: 0-0.5%, Ce: 0-0.5%, B: 0-0.5%, Y: 0-0.5%, P: 0-0.5%, Sr: 0-0.5%, Co: 0-0.5%, Bi: 0-0.5%, In: 0-0.5%, V: 0-0.5%, W: 0-0.5%: 0-5% in total.
2. The plated steel sheet according to claim 1, wherein: The chemical composition of the plating layer includes Mg: 4.5-8 mass %, Si: 0.1-2 mass %, The number density of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more exposed on the surface of the plating layer is 2 The area is 0 to 3.
3. The plated steel sheet according to claim 1, wherein: The chemical composition of Al, Mg and Si in the plating layer is Al: 15-25 mass %, Mg: 4.5-8 mass %, Si: 0.1-2 mass %, The number density of the Ca-Zn phase with an equivalent circle diameter of 1 μm or more exposed on the surface of the plating layer is 2 The area is 0.
4. The plated steel sheet according to any one of claims 1 to 3, wherein The chemical composition of Al, Mg and Si in the plating layer is Al: 15-25 mass %, Mg: 4.5-8 mass %, Si: 0.1-2 mass %, The number density of the Mg-Si-Zn-Al phase with a major diameter of 2 μm or more exposed on the surface of the plating layer is 2 The area is 5 to 150.
5. The plated steel sheet according to any one of claims 1 to 3, wherein The chemical composition of the plating layer is Sn: 0.05-0.5 mass%, In an X-ray diffraction measurement of the coating, a Mg2Sn phase was detected in the coating.
6. The plated steel sheet according to claim 4, wherein: The chemical composition of the plating layer is Sn: 0.05-0.5 mass%, In an X-ray diffraction measurement of the coating, a Mg2Sn phase was detected in the coating.
7. The plated steel sheet according to claim 1, wherein: The plating layer has a chemical composition containing the group A in mass %.
8. The plated steel sheet according to claim 1, wherein The plating layer has a chemical composition containing the B group in mass %.
9. The plated steel sheet according to claim 1, wherein: The number density of the Ca-Zn phase with an equivalent circle diameter of less than 1 μm exposed on the surface of the plating layer is 2 The area is more than 1.
Citation Information
Patent Citations
Plated steel
WO2018139619A1
Plated steel
WO2018139620A1